Deep chlorophyll maximum and plankton community response to oceanic bottom intrusions on the continental shelf in the South Brazilian Bight - Pereira Brandini, Frederico; Nogueira, Miodeli; Simião, Monica; Carlos Ugaz Codina, Juan; Almeida Noernberg, Mauricio (Continental shelf research, 2014)
The continental shelf of the South Brazilian Bight (Lat 23–28.5°S) is subject to bottom intrusions of the oceanic and nutrient-rich South Atlantic Central Waters (SACW) in summer, to compensate for the Ekman transport of surface waters offshore by northeasterly winds. In winter, shelf waters tend to overturn vertically due to tidal circulation and Ekman convergence of outer-shelf waters driven by southerly winds. From 9 November 2005 to 22 June 2006 the shelf off Santa Catarina State was surveyed to investigate hydrographic conditions and the seasonal dynamics of the plankton cross-shelf distribution and community structure. A strong wind-driven onshore bottom intrusion of the SACW with the formation of two independent deep chlorophyll maximum (DCM) layers on the shelf was clear. Chlorophyll concentrations ranged from 0.07 to 6.2mgm−3 and phytoplankton carbon biomass from 0.2 to 511µgCL−1, mostly as large centric diatoms and in spite of the numerical dominance of small pennates. The mid-shelf DCM was 12m thick between 38 and 50m (1–5% of irradiance) with mean chlorophyll concentrations up to 1.8mgm−3. The DCM on the outer shelf was formed between 60 and 70m depth (1–0.01% surface light) by small pennate diatoms and small phytoflagellates, with chlorophyll concentrations of 0.5–0.7mgm−3. Both DCMs were maintained independently from January to April 2006, and dispersed in June due to water column turnover during cold seasons. In the mid-shelf, the DCM was geographically extended towards the inner shelf and became thicker compared to pre- and post-intrusion periods. The freshwater species Aulacoseira granulata and large centric diatoms including the invasive Coscinodiscus wailesii were frequent along the shelf throughout the sampling period. Oncaea waldemari, Ctenocalanus vanus and Oithona plumifera usually dominated the zooplankton, which ranged from 23 to 7970 individualsm−3. Abundances were always higher on the inner shelf regardless of the season of the year. Abundance on the mid-shelf peaked following the onset of the intrusion of the nutrient-rich oceanic SACW in the lower euphotic zone and the enhancement of the DCM. A 6-step circulation model of diatoms coupled with shelf hydrodynamics is proposed as the main mechanism of retention of diatoms in the shelf system. The model suggests that diatoms resuspended in the nearshore are transported offshore by Ekman forces toward oligotrophic waters, where they sink faster due to poor nutrient conditions. Sinking cells find better nutrient conditions in the pycnocline/nutricline layers, become shade-adapted and increase their buoyancy, contributing to the formation of the DCM. Resting cells sinking out of the euphotic zone reach near-bottom layers or the sediments, from where they are carried back onshore by oceanic intrusions of the SACW. We suggest how this hydrodynamic circulation pattern of diatoms may take place in other subtropical shelf systems dominated by western boundary currents. This model of the hydrodynamic loop of diatoms across the shelf of southern Brazil, shows the offshore and onshore transport of diatom cells and their contribution for the formation of deep chlorophyll maximum in the South Brazilian Bight [Display omitted] . •DCM formation studied in relation to oceanic intrusions.•The DCM-associated phytoplankton and zooplankton composition is described.•Plankton assemblages were highly influenced by DCM and on shelf intrusions.•A hydrodynamic model of diatom circulation between coast and mid-shelf is proposed.